Dynamic Control of Microbial Movement by Photoswitchable ATP Antagonists. Issue 30 (12th April 2022) - Thayyil, Sampreeth; Nishigami, Yukinori; Islam, Md. Jahirul; Hashim, P. K.; Furuta, Ken'ya; Oiwa, Kazuhiro; Yu, Jian; Yao, Min; Nakagaki, Toshiyuki; Tamaoki, Nobuyuki
Abstract: Adenosine triphosphate (ATP) is the energy source for various biochemical processes and biomolecular motors in living things. Development of ATP antagonists and their stimuli‐controlled actions offer a novel approach to regulate biological processes. Herein, we developed azobenzene‐based photoswitchable ATP antagonists for controlling the activity of motor proteins; cytoplasmic and axonemal dyneins. The new ATP antagonists showed reversible photoswitching of cytoplasmic dynein activity in an in vitro dynein‐microtubule system due to the trans and cis photoisomerization of their azobenzene segment. Importantly, our ATP antagonists reversibly regulated the axonemal dynein motor activity for the force generation in a demembranated model of Chlamydomonas reinhardtii . We found that the trans and cis isomers of ATP antagonists significantly differ in their affinity to the ATP binding site. Abstract : We synthesized compounds acting as antagonists of ATP and whose activity is reversibly changed by light. When the compound was given to a microorganism moving by flagella, the movement could be changed significantly and reversibly by alternating irradiation of two wavelengths. This means that we can freely control the ATP world that governs the energy flow of living things.